PERAN KONSELOR SEKOLAH DALAM PENDIDIKAN KARAKTER - Wangid, Muhammad Nur (Jurnal Cakrawala Pendidikan, 2010)
Abstract: School Counselor Roles in Character Education. Character educationwas one of the focuses in the system of national education. Therefore, educatorsmust not neglect this. A school counselor, as one of the educators, has to play a rolein character education. Referring to guidance and counseling responsibilities inrelation to students personal, social, academic, and career aspects, a schoolcounselor must not escape from the main duties. Considering that charactereducation is the responsibility of all parties, a school counselor can, independentlyand in collaboration with all school components, play a role in character education.Individually, a school counselor can provide services, such as individual services,individual planning services, and responsive services. In collaboration with otherparties, a school counselor can make a synergy in character education programs.Keywords: school counselor, character education